Parents' Attitudes towards the Reading Culture of the Lower Primary School Students - Nedeljko M. Milanović; Маrina D. Matejević (University of Belgrade, Teacher Education Faculty, 2023)
The aim of this research is to determine the attitudes of parents towards the reading culture of students in the lower grades of primary school. 180 parents from the Republic of Serbia participated in the research. A descriptive method and a theoretical analysis method were applied, while the instrument was created separately for this research. The obtained results show the positive attitudes of parents towards the reading culture of the children in the lower grades of primary school, although most parents believe that there are certain obstacles in the development of reading culture, such as: a low socio-economic status of parents (18.3%), a lack of interest and laziness of both parents and children (17.8%), parents overworked (14.4%), reading is not in trend (8.9%), and digitalization process (7.8%). Also, significant statistical differences were observed between the socio-demographic characteristics of parents and their attitudes towards reading culture. The results show that mothers, more often than fathers, believe that children should read every day. Parents with a higher level of education generally care more about their children's reading culture. Older parents generally believe that children should be influenced by a personal example, while younger parents more often believe that parents should be involved in school activities. The implications of the obtained findings suggest that reading culture must become an imperative today, both in the family environment and in the joint cooperation of parents with the school through the involvement of parents in curricular and extracurricular activities and contents.